Influence of sex on selecting indoor resting sites by Triatoma pallidippennis Stal (Hemiptera: Reduviidae) adults under laboratory and field conditions - Torres - Estrada, José Luis; Martínez - Ibarra, José Alejandro; García - Pérez, Jaime Alejandro (Ecosistemas y Recursos Agropecuarios, 2014)
A study we conducted in order to determine the influece of Triatoma pallidippennis adults sex on some behaviors integrating of vectorial efficiency: Para obtener el articulo completo pueden contactar al Editor de la Revista Ecosistemas y Recursos Agropecuarios en el siguiente correo electrónico era@ujat.mx y se les enviará sin algún costo.